Women Scientists and Managers in Agricultural Research in the Philippines - Brush, Edwin G.; Merrill-Sands, Deborah; Gapasin, Dely P.; Mabesa, Virginia L. (International Service for National Agricultural Research, 1995)
This case study investigates the entry, retention, and achievement of women in agricultural science in the Philippines. It is intended to help research managers and their organizations in developing countries meet the challenges of changing work-force characteristics. It was carried out in four public-sector institutes with a total of almost 300 scientists, 54% of whom are women. The study used survey data, interviews and discussions with 100 staff, and records from two universities. Women are replacing men who have left the public sector for career opportunities in the private sector. Family responsibilities are an important factor leading to retention of women in public-sector jobs, which offer stability, flexibility, and supportive policies. Although women constitute a majority of the workforce, they are underrepresented in top-level positions. Seniority and research output did not explain the discrepancy since men and women have comparable length-of-service and publication records. Data suggest that women's careers are affected more than men's by their status in dual-career families. Women cited delays in training, relocation to follow husbands, and lack of mobility as career constraints. Cultural stereotypes of men's and women's roles within the household continue to color and affect working relationships and appear to limit women's opportunities for advancement into senior positions. We are likely to see increasing participation of women in research organizations in developing countries. Constraints to women's career attainment may persist primarily due to cultural barriers. The study discusses management practices from the Philippines that can assist the effective incorporation of women into a scientific work force.